2009
DOI: 10.1086/605963
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Reproduction, Resource Quality, and Terminal Investment in a Burying Beetle

Abstract: We evaluate the cost-of-reproduction hypothesis in the burying beetle Nicrophorus orbicollis and examine how the importance of this trade-off changes as females age (i.e., the terminal-investment hypothesis). These beetles breed on small vertebrate carcasses, which serve as a food resource for them and their offspring. Consistent with the cost-of-reproduction hypothesis, females manipulated to overproduce offspring suffered a reduction in fecundity and life span when compared to controls, although all reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
199
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(221 citation statements)
references
References 49 publications
14
199
4
1
Order By: Relevance
“…2), perhaps reflecting higher migration cost for smaller individuals (38), lesser total energy reserves, and thereby decreased survival after spawning. However, evolutionary theory also predicts that older females are expected to invest more in the present reproductive opportunity, given their limited number of future reproductive opportunities (39,40) compared with younger females, which may increase their lifetime reproductive success by investing in growth (5). Accordingly, spawning omission may be caused by age-dependent differential energy allocation rather than limited energy reserves per se, and some skippers may be expected to grow more than developing fish in the year of missed migration and spawning.…”
Section: Discussionmentioning
confidence: 99%
“…2), perhaps reflecting higher migration cost for smaller individuals (38), lesser total energy reserves, and thereby decreased survival after spawning. However, evolutionary theory also predicts that older females are expected to invest more in the present reproductive opportunity, given their limited number of future reproductive opportunities (39,40) compared with younger females, which may increase their lifetime reproductive success by investing in growth (5). Accordingly, spawning omission may be caused by age-dependent differential energy allocation rather than limited energy reserves per se, and some skippers may be expected to grow more than developing fish in the year of missed migration and spawning.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in resource allocation would allow females to incur a fitness benefit if they mobilized relatively more somatic tissue to support reproduction during this final bout than in prior reproductive events (Clutton-Brock, 1984). In support of this idea, several studies have observed enhanced reproductive performance during the terminal reproductive bout (Clutton-Brock, 1984;Poizat et al, 1999;Andrade and Kasumovic, 2005;Isaac and Johnson, 2005;Creighton et al, 2009;Weladji et al, 2010;Fisher and Blomberg, 2011). The physiological mechanisms that would allow females to increase somatic tissue mobilization in old age are unclear and warrant future study.…”
Section: Positive Effects Of Reproduction On Bioenergetic Capacitymentioning
confidence: 97%
“…1C). Reproductive performance may increase (Andrade and Kasumovic, 2005;Isaac and Johnson, 2005;Creighton et al, 2009;Weladji et al, 2010) or it may decline (Fig. 1C) (Finn, 1963;Newton et al, 1981;Descamps et al, 2009;Hammers et al, 2015;Warner et al, 2016) during a female's final reproductive event(s).…”
Section: Proposed Physiological Basis For Life-history Patternsmentioning
confidence: 99%
“…Prehatching care includes preparation of the carcass and investment of nutrients in eggs (Rozen et al 2008;Monteith et al 2012), while posthatching care includes brood defense, secretion of antimicrobials, and food provisioning (Eggert et al 1998;Smiseth et al 2003;Rozen et al 2008). Last, there is evidence for a trade-off between investment in current and future reproduction in N. vespilloides and the related Nicrophorus orbicollis: females that overproduce offspring in the first breeding attempt suffer a reduction in fecundity in future breeding attempts (Creighton et al 2009;Ward et al 2009;Billman et al 2014).…”
Section: Introductionmentioning
confidence: 99%